2020
DOI: 10.1680/jgein.20.00019
|View full text |Cite
|
Sign up to set email alerts
|

Effect of infilled materials and arrangements on shear characteristics of stacked soilbags

Abstract: The Shear characteristics of stacked soilbags are related to their interlayer arrangements and properties of the materials with which the bags(geosynthetics) are filled. To study the effects of those factors on the shear strength and failure mode of stacked soilbags, a series of shear tests were conducted. The results show that although the shear failure surface occurred at the horizontal interface between soilbags when they were arranged vertically, it was ladder-like when the soilbags were arranged in a stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…For the subgrade treated with the sand cushion, the settlements recorded after stabilization under the first-, second-, third-, and the fourth-stage loads were 109.39 mm, 122.86 mm, 130.05 mm, and 137.86 mm, respectively, which were greater than those of the soilbag-treated subgrade under corresponding loads. Such differences in settlement are attributed to the staggered arrangement of the soilbags in the upper and lower layers, which have the effect of spreading the stresses, enabling the vertical stresses from the upper layers to be more uniformly distributed to the base [33]. From these observations, it is inferred that the soilbag-treated subgrade exhibited a superior bearing capacity compared to the sand cushion-treated subgrade.…”
Section: Consolidation Model Tests and Tests Resultsmentioning
confidence: 98%
“…For the subgrade treated with the sand cushion, the settlements recorded after stabilization under the first-, second-, third-, and the fourth-stage loads were 109.39 mm, 122.86 mm, 130.05 mm, and 137.86 mm, respectively, which were greater than those of the soilbag-treated subgrade under corresponding loads. Such differences in settlement are attributed to the staggered arrangement of the soilbags in the upper and lower layers, which have the effect of spreading the stresses, enabling the vertical stresses from the upper layers to be more uniformly distributed to the base [33]. From these observations, it is inferred that the soilbag-treated subgrade exhibited a superior bearing capacity compared to the sand cushion-treated subgrade.…”
Section: Consolidation Model Tests and Tests Resultsmentioning
confidence: 98%
“…The shape of the sliding surface has influence over friction resistance between the soil bag layers Fan et al (12). Fan et al ( 13) study showed a containment constructed wall to analyze the slippage stability, and concluding that "the active soil pressure acts upon the wall built with sand bags on their final stage is not linear, but can be calculated from the strength balancing forces of a differential element".…”
Section: Physical and Mechanical Characteristics Studymentioning
confidence: 99%
“…Fan et al ( 13) study showed a containment constructed wall to analyze the slippage stability, and concluding that "the active soil pressure acts upon the wall built with sand bags on their final stage is not linear, but can be calculated from the strength balancing forces of a differential element". In a geotextile bag system, the units disposition in its intermediate layers, and the filling material properties is related to the bags' cutting characteristics (12). doi: 10.25100/iyc.v26i1.13256…”
Section: Physical and Mechanical Characteristics Studymentioning
confidence: 99%
“…Besides, several layers of soilbags form a hard shell layer on the surface of soft foundation [40]. Therefore, its strength and stiffness are greater than that of the soft soil layer under it.…”
Section: Technical Principle Of Soilbagsmentioning
confidence: 99%